Dynamic behavior of a high-rise building under seismic loads for different bearing frame types = Dynamiczne zachowanie się budynku wysokiego pod obciążeniem sejsmicznym dla różnych typów szkieletu budynku - Sakharov, Volodymyr; Lytvyn, Oleksandr; Pidlutskyi, Vasyl (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Paper presents the results of dynamic behavior analysis of a high-rise building under seismic loads as part of the "base-foundation-building" system. Analysis covers different types of reinforced concrete construction with girder frame and non-girder frame. Using modal analysis, paper presents differences in mode shapes and frequencies caused by the presence or absence of girders. Paper also demonstrates variations in the stress-strain state for the vertical bearing structures under the seismic load for different frame types.
Keywords: bearing frame; girder frame; dynamic response; seismic load; modal analysis; numerical methods; soil base; foundations; high-rise buildings; konstrukcja szkieletowa; odpowiedź dynamiczna; obciążenie sejsmiczne; analiza modalna; metody numeryczne; podłoże gruntowe; fundamenty; budynek wysokościowy; rama nośna budynku